Lithic Technologies, Functional Variability, and Settlement Systems in Late Pleistocene Beringia – New Perspectives on a Colonization Process - Heidenreich, Stephan (2014)
The Arctic and sub-Arctic regions of northeastern Asia and northwestern North America – commonly referred to as Beringia – have often been regarded as the point of entry for the peopling of the Americas. This study makes an active contribution to Beringian archaeology by attempting to explain this complex colonization process through an empirical study of altogether 21 assemblages of secondarily modified lithic artifacts from 14 sites in north and central Alaska (Eastern Beringia) and in the Amur River region in the Russian Far East, a potential area of origin for the colonization of (Western) Beringia. The separate late Pleistocene climatic stages between the LGM and the Holocene (i.e. Greenland Stadials and Interstadials GS-2, GI-1, and GS-1) mark the time frame for the study. A review of the current state of research in Beringian archaeology concludes that traditionally separated complexes or industries should not be addressed as representatives of cultural-chronological entities. Instead, the respective assemblages should be regarded as integrated parts within broadly conceived hunter-gatherer mobility patterns. Accordingly, intraassemblage diversity and interassemblage variability are consulted with the aim to reconstruct site activities and occupation histories of the respective camp sites and trans-regional hunter-gatherer settlement systems. The mobility pattern reconstructed for Eastern Beringia in GI-1 and GS-1 is characterized by a two-fold settlement system comprising principal and seasonal habitats. The examined assemblages from the selected sites along the Selemdzha River in the Russian Far East, by contrast, show little variation and probably represent a special purpose subarea within a larger habitat. Eventually, the respective reconstructed land use models are considered from a diachronic perspective and the attempt is made to explain Beringian colonization processes in a two-step model. Die als Beringia bezeichneten (sub-)arktischen Regionen Nordostasiens und Nordwest-Nordamerikas werden oft ...